MULTIOBJECTIVE ERGONOMIC WORKFORCE SCHEDULING UNDER COMPLEX WORKER AND TASK CONSTRAINTS - Wongwien, Tanuchporn; Nanthavanij, Suebsak (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
When workers are assigned to perform a set of tasks with exposure to certain safety/ergonomics hazard, they are sometimes rotated among the tasks periodically within each day so that their daily hazard exposures do not exceed a permissible limit. Usually, workers have unequal task flexibility and skill levels. Assigning the right workers to the right tasks in each period can help to increase the work system productivity. In this paper, we discuss the multiobjective ergonomic workforce scheduling problem with complex worker and task constraints. Three problem objectives are considered: (1) minimizing the number of workers involved in job rotation, (2) maximizing the total productivity, and (3) minimizing the number of worker-task changeovers. An integer linear programming model and a heuristic procedure are presented.